2022
DOI: 10.3390/ijms232416117
|View full text |Cite
|
Sign up to set email alerts
|

Differential Upregulation and Functional Activity of S1PR1 in Human Peripheral Blood Basophils of Atopic Patients

Abstract: Basophils are key effector cells in atopic diseases, and the signaling sphingolipid Sphigosine-1-phosphate (S1P) is emerging as an important mediator in these conditions. The possible interaction of S1P and basophils and the resulting biological effects have not yet been studied. We hypothesize that S1P influences the function of basophils in atopy and aim to elucidate the modes of interaction. S1P receptor (S1PR) expression in human peripheral blood basophils from atopic and non-atopic patients was assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Experiments to analyze changes in calcium flux were performed according to the same procedure as described recently [67]. Purified eosinophils were labeled with 3 µM Fluo-4 (Molecular Probes, Eugine, OR, USA) and stimulated with 0.1, 1, 10, or 100 µM capsaicin (Merck, Darmstadt, Germany) during the measurement.…”
Section: Calcium Flux Experimentsmentioning
confidence: 99%
“…Experiments to analyze changes in calcium flux were performed according to the same procedure as described recently [67]. Purified eosinophils were labeled with 3 µM Fluo-4 (Molecular Probes, Eugine, OR, USA) and stimulated with 0.1, 1, 10, or 100 µM capsaicin (Merck, Darmstadt, Germany) during the measurement.…”
Section: Calcium Flux Experimentsmentioning
confidence: 99%
“…Due to the inhibiting effect of the lipid mediator on chemotaxis, S1P is proposed to have an anti-inflammatory effect on basophils (31).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…SP has also been shown to chemoattract basophils, resulting in the infiltration of basophils into the skin of healthy individuals (49). Recently, it was shown that in healthy donors, basophils migrate towards S1P which was observed in an in vitro study, while in AD patients a chemorepulsive effect was detected (31). It has however, so far not been described if basophils, that migrated into the skin, return to the blood or travel to draining lymph nodes (45,50).…”
Section: Introductionmentioning
confidence: 97%
“…(2023) and Gray et al. (2022). Furthermore, we describe a flow cytometry staining protocol to assess basophil yield, purity, and viability (Support Protocol 1), as well as a staining protocol to visually inspect the purified basophils (Support Protocol 2).…”
Section: Introductionmentioning
confidence: 97%
“…The manufacturers' protocol was modified to use a lower amount of antibody cocktail and magnetic beads, therefore reducing the cost, but still ensuring cell purities to be consistently >96%. We have used this method for publishing our research on basophils in Limberg et al (2023) and Gray et al (2022). Furthermore, we describe a flow cytometry staining protocol to assess basophil yield, purity, and viability (Support Protocol 1), as well as a staining protocol to visually inspect the purified basophils (Support Protocol 2).…”
Section: Introductionmentioning
confidence: 99%